MENUJU PEMBANGUNAN BERBASIS TATA RUANG MELALUI PERENCANAAN LINGKUNGAN BERTETANGGA SECARA PARTISIPATIF Studi Kasus Pelaksanaan Program Pengembangan Lingkungan Berbasis Komunitas (PLP-BK) di Kelurahan Pringapus Kabupaten Semarang - Asnawi Manaf (Diponegoro University, 2011)
It should be questioned especially by scholars in the field of planning that until now planning documents in Indonesia (development or spatial plan) produced with public money, is it already reflecting or relevant to the need of the community? This provocative question got enough attention, now adays. As the evidence, the government has been introducing and applying various participatory planning approaches to ensure greater opportunities for people to take part in decisions making process. One of these is the Community-Based Neighborhood Development Planning Program or in Bahasa Penataan Lingkungan Permukiman Berbasis Komunitas (PLP-BK). This paper try to describe a research result aimed to examine the extent of participatory concepts are applied in the program and then identify obstacles and challenges will be found. Research is conducted by qualitative approach; the case study method was used to take the case of implementation program in PLP-BK in Pringapus Village Semarang District, which is one of 18 pilot projects in Indonesia.From the research conducted, it can be concluded that the participatory approach applied in PLP-BK implementation in the study area had given a great authority for the community in making planning decision, but it still in the spatial rules. Further, this research grouped 2 major issues which still get attention to improve program performance in the future. First, the clarity of the scope of PLP-BK problem program which should be more pointed at the scale of environmental problems, second the full participatory planning contains conflict between the need for Participatory Planning Expert (TAPP) who has competence not only in spatial planning but also on the method of participatory planning becomes urgent.